Household wellbeing in rural Papua New Guinea: Poverty analysis from the 2023 PNG Rural Household Survey - Mahrt, Kristi; Schmidt, Emily; Fang, Peixun; Mukerjee, Rishabh (International Food Policy Research Institute, 2025)
This analysis provides the first poverty assessment using the cost of basic needs approach in Papua New Guinea in 1.5 decades. The cost of basic needs poverty methodology is the standard approach to estimating poverty in low- and middle-income countries. It aims to reflect the cost of a food basket and nonfood needs to secure a healthy life and minimum standard of living. Using the cost of basic needs approach, we calculate and compare two poverty measurements. First, we compute a standard (traditional) cost of basic needs poverty line where the food poverty line is defined by a dietary energy (calorie) threshold. Second, we extend the standard cost of basic needs approach to calculate a healthy diet food poverty line that meets both the dietary energy threshold, as well as recommended nutrition targets.